2014
DOI: 10.1038/srep04659
|View full text |Cite
|
Sign up to set email alerts
|

A simple, inexpensive method for preparing cell lysates suitable for downstream reverse transcription quantitative PCR

Abstract: Sample nucleic acid purification can often be rate-limiting for conventional quantitative PCR (qPCR) workflows. We recently developed high-throughput virus microneutralization assays using an endpoint assessment approach based on reverse transcription qPCR (RT-qPCR). The need for cumbersome RNA purification is circumvented in our assays by making use of a commercial reagent that can easily generate crude cell lysates amenable to direct analysis by one-step RT-qPCR. In the present study, we demonstrate that a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 17 publications
0
69
0
Order By: Relevance
“…Generally, it has been shown that miRNAs are highly stable in cell lysates and can be stored at −20 and/or −80°C for days. 18,19 In our proof-ofconcept test of freeze−thaw cell lysate, the endogenous miR-21 signal was decreased by ∼50% compared to fresh cell lysates ( Figure S4). This signal decrease is probably due to freeze/ thaw temperatures (here, −20°C/room temperature) or absence of RNase inhibitor; a previous study demonstrated that RNA stability was enhanced when stored at −80°C or thawed at 4°C or RNase inhibitor added.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, it has been shown that miRNAs are highly stable in cell lysates and can be stored at −20 and/or −80°C for days. 18,19 In our proof-ofconcept test of freeze−thaw cell lysate, the endogenous miR-21 signal was decreased by ∼50% compared to fresh cell lysates ( Figure S4). This signal decrease is probably due to freeze/ thaw temperatures (here, −20°C/room temperature) or absence of RNase inhibitor; a previous study demonstrated that RNA stability was enhanced when stored at −80°C or thawed at 4°C or RNase inhibitor added.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Previously, Ho et al has reported microRNA LODs of 200 cells, 19 which is within an order of magnitude of the LOD obtained with our hydrogel-based detection. Even though some recent studies on direct miRNA measurements demonstrate high sensitivity (1−1000 cells), 18,20 their measurements are based on target-based amplification of qRT-PCR. This targetbased amplification often introduces sequence bias.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were washed with cold PBS once and lysed in the Real-time cell lysis buffer containing 10mM Tris pH 7.4, 0.25% Igepal CA-630, and 150mM NaCl for 5 mins [18]. Cell lysates were directly used for real-time as the amplification templates.…”
Section: Real-time Quantitative Pcr (Rt-qpcr)mentioning
confidence: 99%
“…Cell lysate was then prepared by aspirating the culture media using the GNF Systems (San Diego, CA) WDII plate washer, and then the cells were washed with 100 μL of cold PBS, removing as much of the wash solution from each well as possible. The cells were then lysed by the addition of 15 μL of lysis buffer (10 mM Tris-HCl, pH 7.4, 0.25% IGEPAL, 150 mM NaCl, final concentrations, dissolved using DNase/ RNase-free water, all from Sigma) as described by Shatzkes et al 20 The cells were lysed by incubation for 30 min at room temperature. During this time, the PCR master mix (Roche Diagnostics, Indianapolis, IN) was prepared, including Taqman primers for actin and CYR61, and then 900 nL of the master mix was dispensed to the Roche LightCycler 1536 well assay plate using the Thermo Combi nL.…”
Section: Qpcr To Measure Cyr61 Gene Expressionmentioning
confidence: 99%